Space-saving rainwater harvesting tanks for double story houses in Kuching, Sarawak - Kuok Kuok, King; Chan Chiu, Po (International Journal of Engineering and Technology, 2019)
Rainwater harvesting (RWH) system is a popular low impact development urban design tool for storing non-potable water. However, it is not successfully implemented in Malaysia due to its conventional look and space occupancy. Hence space-saving RWH tanks such as VODA tank, Thin tanks, Rainwater HOG, Water Butts and Rainwater Bladder Tank are introduced in this study to investigate its feasibility for replacing the conventional RWH tank. The study focusing on different types of double-storey houses named as terrace intermediate, terrace corner, semi-detached and detached houses located at Kuching, Sarawak, Malaysia. Modelling simulation is carried out with Tangki NAHRIM software, developed by National Hydraulic Research Institute of Malaysia (NAHRIM). Results show the optimum size of RWH tank for double-storey houses in Kuching is 2m3. The optimum size of a conventional tank obtained can be dispersed into various types of space-saving RWH tanks at different locations including balcony, external walls, backyard of the houses or even near the side of the fences. It was found the most preferable tank is 1000L and 2000L Thintank, that can be installed vertically beside the fencing at the front car porch and backyard which reduces the space occupied by tanks.Â Â